THE ROLE OF FRUGAL INNOVATION, CULTURAL INTELLIGENCE, ALTERNATIVE FINANCING, AND REGULATORY AGILITY IN ENHANCING BUSINESS ADAPTABILITY IN CREATIVE INDUSTRY - Judijanto, Loso; Suwandana, I Made Adi; Zukfikri, Agung (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study investigates the influence of frugal innovation, cultural intelligence, alternative financing, and regulatory agility on business adaptability in the creative industry. Using a quantitative approach with data collected from 250 creative business actors in Indonesia, the study applies Structural Equation Modeling (PLS-SEM) to test the proposed relationships. The results reveal that all four variables significantly and positively affect business adaptability, with regulatory agility having the highest impact. Frugal innovation enables efficient resource utilization, cultural intelligence enhances cross-cultural responsiveness, alternative financing improves financial flexibility, and regulatory agility creates an enabling environment for adaptation. These findings emphasize the importance of a multidimensional strategy that combines internal capabilities and external enablers to strengthen adaptability. The study offers theoretical contributions and practical implications for entrepreneurs, policymakers, and stakeholders in the creative economy seeking resilience and long-term growth.